Head to head comparison of (18F)SiTATE versus (18F])DOPA-PET in patients with neuroendocrine tumors - Roll, Wolfgang; Hadjitheodorou, Panayiotis; Alevroudis, Emmanouil; Kyrou, Kyriaki; Adamou, Giorgos; Fesas, Andreas; Wängler, Björn; Wängler, Carmen; Schirrmacher, Ralf; Pourkhessalian, Mohammad R.; Kalogirou, Charalambia; Tsechelidis, Ioannis; et al. (European journal of nuclear medicine and molecular imaging, 2025)
In neuroendocrine tumors molecular imaging methods play a key role, either targeting the somatostatin receptor or catecholamine pathways. [18F]SiTATE is a somatostatin receptor-targeting peptide that uses silicon fluoride acceptor (SiFA) radiochemistry, overcoming disadvantages of Gallium-68 labelled DOTA compounds. Here we present the first prospective data of [18F]SiTATE compared to [18F]DOPA-PET in NET patients.
Im Titel ist "18F" in eckigen Klammern geschrieben und hochgestellt
Online veröffentlicht: 26. September 2025
Gesehen am 30.10.2025